PENGARUH AUTHENTIC ATMOSPHERICS TERHADAP BEHAVIORAL INTENTION DENGAN POSITIVE EMOTION DAN CUSTOMER EXPERIENCE SEBAGAI VARIABEL MEDIASI PADA GALERI KOPI INDONESIA DI ACEH TENGAH - Khafijas Aprianti; Rizki Amalia (Departemen Manajemen, 2022)
This study aims to determine the effect of Authentic Atmospherics on Behavioral Intention mediated by Positive Emotion and Customer Experience on visitors to the Indonesian Coffee Gallery in Central Aceh. The sample used in this study was 150 visitors who were selected through non-probability sampling technique. Data collected through questionnaires and analyzed using Partial Least Square (PLS). The results of the analysis show that Authentic Atmospherics has an effect on Behavioral Intention, Authentic Atmospherics has an effect on Positive Emotion, Authentic Atmospherics has an effect on Customer Experience, Positive Emotion has an effect on Behavioral Intention, Customer Experience has an effect on Behavioral Intention, Positive emotional as a mediating variable with Authentic Atmoshpherics having an effect on Behavioral Intention, Customer Experience as mediating variables with Authentic Atmospherics affect Behavioral Intention.